Förutsättningar för ämnesspecifik läsförståelse i samhällskunskap i grundskolan - Åsa af Geijerstam; Jenny Wiksten Folkeryd; Yvonne Hallesson; Pia Raattamaa Visén (Educare)
This paper deepens the understanding of conditions for students' subject-specific reading comprehension created through different ways of working with reading in civic education, and the support students thus get to read verbal texts. Motivation for the study is found in an increasing need for knowledge about reading in various school subjects, and theoretical foundation is found in New Literacy Studies and disciplinary literacy. Video recordings were analyzed from lessons in three different schools and six different classes (ca 100h in total). The schools worked with reading in different ways, two schools used different models for teaching reading and one school did not use any particular model. The material was analyzed using thematic content analysis. Seven different functions for reading were identified together with reading materials. Furthermore, we analyzed which text levels were in focus. Results show that the classrooms where teachers work according to special models give clearer support to read and comprehend longer coherent verbal texts by using this type of texts and working with them through a variety of functions for reading activities, activities general for several subjects as well as more subject specific activities.